Human Resources as Ethical Gatekeepers: Hiring Ethics and Employee Selection - Villegas, Salvador; Lloyd, Robert A.; Tritt, Addison; Vengrouskie, Edward F. (Journal of Leadership, Accountability and Ethics, 2019)
The act of hiring an individual can have considerable ethical and legal implications for an organization. To better identify the concepts that influence hiring and employment selection ethics, a review of the recent literature found several areas of importance for both academics and hiring managers alike. Past researchers claim hiring managers are influenced by the concepts of moral obligation, diversity, antidiscrimination, integrity, and employment fairness whenever they embark on hiring new personnel. Awareness and action in these areas will lead to motivating factors which can change attitudes, while allowing ethical hiring practices to shape organizational culture. The literature presents a dichotomy of understanding that when organizations use a defined ethical hiring standard, employers are more likely to recruit and hire ethical candidates. This understanding creates the assumptions that managers are obligated with the responsibility of being ethical gatekeepers for their respective organization.